PENYIDIKAN TINDAK PIDANA PENYELUNDUPAN BAWANG ILEGAL OLEH PENYIDIK PEGAWAI NEGERI SIPIL BALAI KARANTINA PERTANIAN KELAS I PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 1992 TENTANG KARANTINA HEWAN, IKAN, DAN TUMBUHAN - Nurul Afifah; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Onions are used fresh food of Indonesian society as a culinary spice supplement. Needs onions in Riau Province is very high, while the local onion production can not meet the needs of the community onions. Therefore do import onions from overseas such as Thailand. But in practice, many violations committed by businesses onions with committing a criminal act of smuggling onions to the province of Riau. Therefore, the active role of civil servant investigators (investigators) Institute for Agriculture Quarantine Class I Pekanbaru in terms of supervision and enforcement is needed. The purpose of this thesis, namely: First, the process of investigation of criminal smuggling of onions illegal by investigators Institute for Agriculture Quarantine Class I Pekanbaru Second, obstacles to the investigation of criminal smuggling of onions illegal by investigators Institute for Agriculture Quarantine Class I Pekanbaru Third, efforts to overcome obstacles in the investigation the crime of illegal smuggling of onions by investigators Institute for Agriculture Quarantine Class I Pekanbaru.This type of research used in writing this law is the law of sociological research that in this study the authors directly conduct research on the locations or places studied in order to give a complete picture of the issues examined. Meanwhile, the population and the sample is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data tertiary, data collection techniques in this study by observation, interview and literature studyFrom the research there are three main things that can be inferred. First, the process of investigation of criminal smuggling of illegal onions by investigators Agriculture Quarantine Center Class I Pekanbaru not run optimally because the main actors (Intelctual dader) was not found. Therefore the criminal cases of smuggling of onions illegal still a lot going on in the province of Riau, Second, barriers in conducting criminal investigations of smuggling onions illegal ie, Act Quarantine no longer relevant to the quarantine modern, factors geographic location of Riau province close to the Strait of Malacca which is a line of international trade, a factor of coordination with related parties running with no opptimal, Third, efforts made to overcome these barriers is to renew the Quarantine Act, increased coordination with relevant parties such conduct coordination meetings, etc .. Suggestions Writer, first, to the government to improve performance in the areas of quarantine, and increased coordination with the relevant parties, Second, Opening Dumai port as the inclusion of fresh food, Third, to the community to increase awareness of the law by providing reports when aware of criminal acts of illegal smuggling of onions.Keywords: Investigation - Crime - Smuggling Onions